Development of soft gripper based on bistable dome shell effect - Chentsov, Oleh; Grynevych, Oksana (My University, 2024)
This study aimed to investigate the principle of implementation of the bistable shell dome effect in a traditional soft gripper based on FEA technology and estimate approximate parameters and geometry for greater performance.

Це дослідження мало на меті дослідити принцип реалізації ефекту купола бістабільної оболонки в традиційному м’якому захопленні на основі технології FEA та оцінити приблизні параметри та геометрію для кращої продуктивності.
Keywords: soft gripper; bionic grippe; dome shell; bistable gripper; м'який пристрій захоплення; м'який гріпер; еластична куполоподібна оболонка